Consider the equation StartFraction 5 Over 3 EndFraction v plus 4 plus StartFraction 1 Over 3 EndFraction v equals 8. v + 4 + StartFraction 5 Over 3 EndFraction v plus 4 equals 8 minus StartFraction 1 Over 3 EndFraction v. v = 8. What is the resulting equation after the first step in the solution? v +4 = 8 – v StartFraction 4 Over 3 EndFraction v plus 4 equals 8.v +4 = 8 4 + v = 8 – 4 plus v equals 8 minus StartFraction 5 Over 3 EndFraction v.v 2v + 4 = 8

Respuesta :

Answer:

Option d.

Step-by-step explanation:

The given equation is

[tex]\frac{5}{3}v+4+\frac{1}{3}v=8[/tex]

We need to find the resulting equation after the first step in the solution.

First step: Combined like terms.

[tex](\frac{5}{3}v+\frac{1}{3}v)+4=8[/tex]

[tex](\frac{5}{3}+\frac{1}{3})v+4=8[/tex]

[tex](\frac{5+1}{3})v+4=8[/tex]

On simplification we get

[tex](\frac{6}{3})v+4=8[/tex]

[tex]2v+4=8[/tex]

The resulting equation after the first step in the solution is 2v+4=8.

Therefore, the correct option is d.

Answer: Option  D

(D)  2v  + 4 = 8

Step-by-step explanation: